2015
DOI: 10.1007/s13244-015-0407-z
|View full text |Cite
|
Sign up to set email alerts
|

Beyond PET/CT in Hodgkin lymphoma: a comprehensive review of the role of imaging at initial presentation, during follow-up and for assessment of treatment-related complications

Abstract: ObjectiveThe purpose of this article is to provide a comprehensive review of the role of imaging modalities other than PET/CT in the management of Hodgkin lymphoma (HL). PET/CT is the imaging modality of choice in the management of Hodgkin’s lymphoma (HL). However, imaging modalities other than PET/CT such as plain radiographs, ultrasound, CT, MRI and nuclear imaging can help in various stages of clinical management of HL, including the initial workup and post-treatment surveillance. Both CT and MRI help in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 75 publications
(75 reference statements)
0
19
0
Order By: Relevance
“…Use of FDG PET/CT often upstages both Hodgkin lymphoma and NHL compared with conventional CT (40,44,45). Both Hodgkin lymphoma and NHL cells are 18 F-FDG avid (46). In general, lymphoma is 18 F-FDG avid: a study of 766 patients found that overall 94% of all lymphomas were 18 F-FDG avid; notable exceptions were peripheral T-cell lymphoma (90%), small lymphocytic lymphoma (83%), enteropathy-type T-cell lymphoma (67%), splenic marginal zone lymphoma (67%), mucosaassociated lymphoid tissue (MALT) marginal zone lymphoma (54%), lymphomatoid papulosis (50%), and primary cutaneous anaplastic large T-cell lymphoma (40%) (47).…”
Section: Musculoskeletal Imaging Manifestations Of Hematologic Malignmentioning
confidence: 99%
“…Use of FDG PET/CT often upstages both Hodgkin lymphoma and NHL compared with conventional CT (40,44,45). Both Hodgkin lymphoma and NHL cells are 18 F-FDG avid (46). In general, lymphoma is 18 F-FDG avid: a study of 766 patients found that overall 94% of all lymphomas were 18 F-FDG avid; notable exceptions were peripheral T-cell lymphoma (90%), small lymphocytic lymphoma (83%), enteropathy-type T-cell lymphoma (67%), splenic marginal zone lymphoma (67%), mucosaassociated lymphoid tissue (MALT) marginal zone lymphoma (54%), lymphomatoid papulosis (50%), and primary cutaneous anaplastic large T-cell lymphoma (40%) (47).…”
Section: Musculoskeletal Imaging Manifestations Of Hematologic Malignmentioning
confidence: 99%
“…Despite the increased use of position emission tomography-computed tomography (PET-CT), its role in surveillance imaging remains under debate (1,2). PET-CT imaging is superior to CT alone in detecting active disease and therefore plays a major role in determining response to therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Calcifications in untreated lymphoma are very rare, occurring in <1% of patients, and are associated with aggressive subtypes of Uptake markedly ( > 2-3×) higher than liver and/or new lesions X New areas of uptake unlikely related to lymphoma HL. 30 Dystrophic nodal calcifications may develop in 2% to 8% of patients treated with radiation or chemotherapy (Fig. 10).…”
Section: Calcified Lymph Nodesmentioning
confidence: 99%
“…These carry a cause-specific mortality of ~10%. 30 Complications may be acute or chronic and include pericarditis, cardiomyopathy, heart failure, coronary artery disease, and valvular heart disease (Fig. 11).…”
Section: Radiation-induced Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation